Thermal Comfort In A Closed Air Conditioned ICT Laboratory At Ungku Omar Polytechnic Malaysia - Ahmad Rasdan, Ismail (2010)

(untitled)
This paper presents an integrated experimental study of the environmental comfort in a Closed Air Conditioned ICT Laboratory at Ungku Omar Polytechnic, Malaysia. The ICT laboratory is considered as an indoor environment. The study had been carried out by the use of custom made Thermal Comfort Measurement (TCM) equipment in order to investigate the level of thermal in this laboratory, level of CO2, pressure, humidity, wind speed, ambient temperature and globe temperature. All the simultaneous parameters measured were then compared to the standard or guidelines produced by National Institue Of Safety and Health (NIOSH) as well as American Conference of Governmental Industrial Hygienists (ACGIH). The study revealed that the level of CO2 in ICT Laboratory exceeded the hazardous level thus can produce the negative impact to the productivity of the users.